Impact of concomitant replacement of the ascending aorta in patients undergoing aortic valve replacement on operative morbidity and mortality. (9th October 2021) - Winkler, Andreas; Puiu, Paul; Krombholz-Reindl, Philipp; Vötsch, Andreas; Steindl, Johannes; Neuner, Matthias; Kirnbauer, Michael; Seitelberger, Rainald; Gottardi, Roman
Abstract: : OBJECTIVES: The aim of this study was to evaluate the impact of concomitant ascending aortic replacement on operative morbidity and mortality in patients undergoing aortic valve replacement (AVR). METHODS: We retrospectively analysed our institutional database for all patients undergoing elective isolated AVR and AVR with concomitant replacement of the ascending aorta between January 2009 and May 2020. Patients undergoing surgery for infective endocarditis or requiring hypothermic circulatory arrest were excluded. A 3:1 propensity matching was performed for 688 patients to compare isolated AVR (120 patients) with AVR + ascending aortic replacement (40 patients). RESULTS: There were significant differences in median cardiopulmonary bypass (CPB) time [92.5 (75–114) vs 118.5 (104–131) min; P < 0.001], median aortic cross-clamp time [65.0 (51.5–78.5) vs 84.5 (77–94) min; P < 0.001] and median intensive care unit stay [1 (1–3) vs 2 (1–6) days; P < 0.01]. There was no significant difference in the use of intraoperative and postoperative blood products, re-exploration for bleeding, postoperative atrial fibrillation, acute renal failure, incidence of stroke, perioperative myocardial infarction and 30-day mortality. CONCLUSIONS: Concomitant replacement of the ascending aorta significantly prolongs CPB and aortic clamp times but does not increase operative morbidity and mortality. Therefore, replacement of a dilated ascending aorta appears to be the most durable and safest treatment option in patients undergoing AVR with an aneurysmatic ascending aorta. Abstract : Since the first description of an aortic valve replacement (AVR) with concomitant replacement of the ascending aorta by Wheat et al. in 1964 [1], there is ongoing debate about the best surgical approach to treat an aneurysmatic ascending aorta.